Use of miRNAs as Biomarkers in Sepsis - Raluca Dumache; Alexandru Florin Rogobete; Ovidiu Horea Bedreag; Mirela Sarandan; Alina Carmen Cradigati; Marius Papurica; Corina Maria Dumbuleu; Radu Nartita; Dorel Sandesc (Analytical Cellular Pathology)
Sepsis is one of the most common causes of death in critical patients. Severe generalized inflammation, infections, and severe physiological imbalances significantly decrease the survival rate with more than 50%. Moreover, monitoring, evaluation, and therapy management often become extremely difficult for the clinician in this type of patients. Current methods of diagnosing sepsis vary based especially on the determination of biochemical-humoral markers, such as cytokines, components of the complement, and proinflammatory and anti-inflammatory compounds. Recent studies highlight the use of new biomarkers for sepsis, namely, miRNAs. miRNAs belong to a class of small, noncoding RNAs with an approximate content of 19–23 nucleotides. Following biochemical and physiological imbalances, the expression of miRNAs in blood or other body fluids changes significantly. Moreover, its stability, specificity, and selectivity make miRNAs ideal candidates for sepsis biomarkers. In conclusion, we can affirm that stable species of circulating miRNAs represent potential biomarkers for monitoring the evolution of sepsis.